2009
DOI: 10.1523/jneurosci.2030-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Early Neurite Morphogenesis by the Na+/H+ Exchanger NHE1

Abstract: The ubiquitously expressed Na ϩ /H ϩ exchanger NHE1 plays an important role in regulating polarized membrane protrusion and directional motility in non-neuronal cells. Using NGF-differentiated PC12 cells and murine neocortical neurons in vitro, we now show that NHE1 plays a role in regulating early neurite morphogenesis. NHE1 was expressed in growth cones in which it gave rise to an elevated intracellular pH in actively extending neurites. The NHE1 inhibitor cariporide reversibly reduced growth cone filopodia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 81 publications
3
20
0
Order By: Relevance
“…Of interest, shNHE1 cells showed a small but significant increase in the number of cells forming neurites (Figure 8, A and C), a trend opposite to that observed in shNHE5 cells. However, in shNHE1 cells that did form neurites, the mean total neurite number and length were significantly reduced (Figure 8, A–D), in agreement with our previous study showing that pharmacological inhibition or genetic ablation of NHE1 adversely affect neurite elongation and branching (Sin et al. , 2009).…”
Section: Resultssupporting
confidence: 92%
“…Of interest, shNHE1 cells showed a small but significant increase in the number of cells forming neurites (Figure 8, A and C), a trend opposite to that observed in shNHE5 cells. However, in shNHE1 cells that did form neurites, the mean total neurite number and length were significantly reduced (Figure 8, A–D), in agreement with our previous study showing that pharmacological inhibition or genetic ablation of NHE1 adversely affect neurite elongation and branching (Sin et al. , 2009).…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have shown that Na + entry may cause an increase in cytosolic Ca 2+ through either Na + /Ca 2+ exchangers or activation of voltage-gated Ca 2+ channels 17,53, thereby activating Ca 2+ -dependent signaling mechanisms. Moreover, Na + entry via Na + /H + exchange may cause changes in intracellular pH, and thereby regulate many cellular functions including enzyme activity, neuronal growth and death 10,18,70,71,88,89. A recent study showed that Na + influx plays an important role in the onset of anti-Fas-induced apoptosis and that blocking Na + influx may rescue programmed cell death in Jurkat cells 19.…”
Section: Na+ In the Process Of Tissue-injurymentioning
confidence: 99%
“…In axolotl oocytes, a flow of H þ has been measured which constituted the major portion of depolarization-activated outward current (Barish and Baud, 1984). Recently, data were reported on the role of NHE1 in neurite morphogenesis, directional migration in primary cilia, and in differentiation of cardiomyocytes (Li et al, 2009;Schneider et al, 2009;Sin et al, 2009). Our experiments revealed that H þ content is regulated gradually, as B<S¼T in 6 and 24 hpa tails, and B¼S<T in 48 hpa tails.…”
mentioning
confidence: 99%